ASSESSING THE IMPACT OF DIGITAL LEARNING ON ACHIEVING SDG 4 IN HIGHER EDUCATION IN PAKISTAN - Sain, Zohaib Hassan; Nurtina, Sitti (International Interdisciplinary Conference on Sustainable Development Goals, 2024)
Digital learning integration in higher education is a crucial approach to support the attainment of SDG 4, which aims to provide inclusive and fair quality education for everyone. This research aims to evaluate the influence of digital learning programs on the attainment of Sustainable Development Goal 4 in higher education institutions in Pakistan. Implementing a mixed-methods research approach, the study included a comprehensive survey of 384 individuals, including students, teachers, and administrators from various institutions. Additionally, semi-structured interviews were performed with relevant stakeholders. For quantitative analysis, the sample size was determined using Cochran's method. The results demonstrate a strong and positive correlation between digital learning programs and achieving Sustainable Development Goal 4. The regression analysis produced an F-value of 15.47 and a p-value of less than 0.001. Analysis of descriptive data reveals that the average efficacy of digital learning is 3.8 out of 5 points, with significant variations between urban and rural institutions (ANOVA, F = 23.72, p < 0.001). A thematic analysis of qualitative data reveals significant obstacles, such as infrastructure and digital literacy deficiencies, and emphasises the need for institutional preparedness and legislative backing. The research findings indicate that while digital learning benefits the attainment of Sustainable Development Goal 4, specific measures are necessary to tackle the digital literacy gap and improve the quality of digital education. The implications of these results are of great importance for policymakers and educators in their efforts to advance fair access and excellence in higher education by using digital learning methodologies.